Quantum Confinement and Thickness‐Dependent Electron Transport in Solution‐Processed In2O3 Transistors. (4th October 2020) - Isakov, Ivan; Faber, Hendrik; Mottram, Alexander D.; Das, Satyajit; Grell, Max; Regoutz, Anna; Kilmurray, Rebecca; McLachlan, Martyn A.; Payne, David J.; Anthopoulos, Thomas D.
Abstract: The dependence of charge carrier mobility on semiconductor channel thickness in field‐effect transistors is a universal phenomenon that has been studied extensively for various families of materials. Surprisingly, analogous studies involving metal oxide semiconductors are relatively scarce. Here, spray‐deposited In2 O3 layers are employed as the model semiconductor system to study the impact of layer thickness on quantum confinement and electron transport along the transistor channel. The results reveal an exponential increase of the in‐plane electron mobility ( µ e ) with increasing In2 O3 thickness up to ≈10 nm, beyond which it plateaus at a maximum value of ≈35 cm 2 V −1 s −1 . Optical spectroscopy measurements performed on In2 O3 layers reveal the emergence of quantum confinement for thickness <10 nm, which coincides with the thickness that µ e starts deteriorating. By combining two‐ and four‐probe field‐effect mobility measurements with high‐resolution atomic force microscopy, it is shown that the reduction in µ e is attributed primarily to surface scattering. The study provides important guidelines for the design of next generation metal oxide thin‐film transistors. Abstract : The electron mobility in In2 O3 transistors fabricated via spray pyrolysis decreases with reduced channel thickness. Evidence for quantum confinement in these ultra‐thin layers is gathered and the dramatic mobility decrease is correlated to the In2 O3 surface topography and explained by invoking a modified surface roughness scattering carrier model.